Positive Bacterial Culture among Adults with Suspected Urinary Tract Infections Presenting to the Department of Medicine of a Tertiary Care Centre - Bishnu Jwarchan; Subash Sapkota; Durga Dhungana; Anil Dhakal (Journal of Nepal Medical Association, 2024)
Introduction: Urinary tract infections are the most common infections encountered in clinical practice. Treatment needs to take into account the likely organism, comorbidities and local antibiotic sensitivity pattern. This study aimed to find the prevalence of positive bacterial culture among adults with suspected urinary tract infections presenting to the department of medicine of a tertiary care centre.